Improved biological activity of a single chain antibody fragment against human epidermal growth factor receptor 2 (HER2) expressed in the periplasm of Escherichia coli - Akbari, V.; Sadeghi, H. M. M.; Jafarian-Dehkordi, A.; Abedi, D.; Chou, C. P. (Protein Expression and Purification, 2015)
A novel monoclonal antibody against human epidermal growth factor receptor 2 (HER2), i.e., pertuzumab (Perjeta (R)) developed by Genentech, has been verified to be effective in treating metastatic HER2-overexpressing breast cancer. The fact that the presence of the Fc region of the anti-HER2 is uncritical for growth inhibition of tumor cells suggests the potential biological activity of the associated antibody fragments. In the present study, we report functional expression of anti-HER2his-scFv, a single-chain variable fragment (scFv) derived from pertuzumab, in the periplasm of Escherichia coli and its purification. Biological activity of the soluble scFv produced in this manner was characterized using immunofluorescent staining, immunocytochemistry, flow cytometry and cytotoxicity assay. The effect of anti-HER2his-scFv on HER2 dimerization was also assessed by tyrosine kinase assay. It was observed that the purified scFv had a high specificity and affinity to HER2 receptors expressed on the surface of tumor cells with a selective cytotoxic effect on HER2-overexpressing SK-OV-3 cells. In addition, anti-HER2his-scFy was able to suppress phosphorylation of HER2 in the presence of heregulin. The results suggest that anti-HER2his-scFv can be a potential candidate for various therapeutic and diagnosis applications. (C) 2015 Elsevier Inc. All rights reserved.